TAFSIR AYAT-AYAT VEGETARIAN - Immamah; Luthfi Raziq (Jurnal Studi Qur'an dan Tafsir, 2024)
Both al-Quran and hadits are considered capable of being the guidance for the various problems of humans, including dietary habits. In spite of the fact that the term” vegetarian” is inexplicitly mentioned in al-Quran, the basic concepts concerning health and the welfare of the body are reflected within lots of verses. Regarding vegetarian dietary habits are still considered ineffective by some people due to a lack of deep understanding, this comprehension needs further research. This research aims to discuss the vegetarian concept from the perspective of al-Quran as the rahmatan lil 'alamin religion teaches people about welfare life. This research is a literature review with interpretative content analysis as a data analysis method to know the social events in accord with the interpretation of verses concerning vegetarianism; hence, this research can answer the problems well. This research is aimed to analyze the interpretations of ulama concerning verses about vegetarianism. From this research, it is concluded that instead of making vegetarian dietary habits an obligation, al-Quran regards it as an advisable choice for health. Vegetarians think that the reason for health is relevant and in accord with Islamic values, all the more that health is significant to support daily life activity. This research also found that some vegetarian dietary habits need to be mulled over in the context of al-Quran and to be in accordance with Islamic values.